Textile-Based Flexible Capacitive Pressure Sensors: A Review - Min Su; Pei Li; Xueqin Liu; Dapeng Wei; Jun Yang (Nanomaterials, 2022)
Flexible capacitive pressure sensors have been widely used in electronic skin, human movement and health monitoring, and human–machine interactions. Recently, electronic textiles afford a valuable alternative to traditional capacitive pressure sensors due to their merits of flexibility, light weight, air permeability, low cost, and feasibility to fit various surfaces. The textile-based functional layers can serve as electrodes, dielectrics, and substrates, and various devices with semi-textile or all-textile structures have been well developed. This paper provides a comprehensive review of recent developments in textile-based flexible capacitive pressure sensors. The latest research progresses on textile devices with sandwich structures, yarn structures, and in-plane structures are introduced, and the influences of different device structures on performance are discussed. The applications of textile-based sensors in human wearable devices, robotic sensing, and human–machine interaction are then summarized. Finally, evolutionary trends, future directions, and challenges are highlighted.